2019
DOI: 10.3324/haematol.2019.220889
|View full text |Cite
|
Sign up to set email alerts
|

Somatic mutations and T-cell clonality in patients with immunodeficiency

Abstract: Common variable immunodeficiency and other late-onset immunodeficiencies often co-manifest with autoimmunity and lymphoproliferation. The pathogenesis of most cases is elusive, as only a minor subset harbors known monogenic germline causes. The involvement of both B and T cells is however implicated. To study whether somatic mutations in CD4+ and CD8+ T cells associate with immunodeficiency, we recruited 17 patients and 21 healthy controls. Eight patients had late-onset common variable immunodeficiency and nin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Some of the mutations, especially in white blood cells, may contribute to chronic inflammation and autoimmunity (15)(16)(17). This hypothesis is supported by the identification of somatic mutations in the circulating, cytotoxic CD8+ and CD4+ lymphocytes in RA, Felty's syndrome, aplastic anemia, multiple sclerosis, chronic graft-versus-host-disease (cGVHD) and common variable immune deficiency patients (16)(17)(18)(19)(20)(21)(22). The mutation harboring CD8+ lymphocyte clones in RA are stable, cytotoxic effector memory cells (16).…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Some of the mutations, especially in white blood cells, may contribute to chronic inflammation and autoimmunity (15)(16)(17). This hypothesis is supported by the identification of somatic mutations in the circulating, cytotoxic CD8+ and CD4+ lymphocytes in RA, Felty's syndrome, aplastic anemia, multiple sclerosis, chronic graft-versus-host-disease (cGVHD) and common variable immune deficiency patients (16)(17)(18)(19)(20)(21)(22). The mutation harboring CD8+ lymphocyte clones in RA are stable, cytotoxic effector memory cells (16).…”
Section: Introductionmentioning
confidence: 94%
“…Calling of somatic variants from whole-exome sequencing data was performed similar to our previous study (17) and included mapping reads against GRCh38 reference with BWA (27) and calling variants with the GATK toolkit and MuTect2 (28).…”
Section: Variant Identificationmentioning
confidence: 99%
“…The germline mutations of the genes associated with CVID are heterogenous, and only 30-50% of patients with CVID were positive for germline mutations, such as NFKB1 in B-cell-signaling pathways, 5,6 while genetic abnormalities are still unknown in a significant proportion of CVID patients. In this study, Savola et al 4 identified germline TAC1 mutations in CVID patients, and STAT3 and ADA2 mutations in other immunodeficient patients. What role the somatically mutated T cells play in CVID and other immunodeficient states associated with these genetic backgrounds remains unclear.…”
mentioning
confidence: 64%
“…In this issue of Haematologica, Savola et al 4 investigated the somatic mutations of T cells from patients with congenital immunodeficiency, including CVID, using deep amplicon sequencing with 2,355 gene panels and a T-cell receptor (TCR) b gene analysis to seek possible relation-ships between genetic alterations and T-cell abnormalities in these diseases. They found that 6 of 8 patients with CIVD harbored somatically mutated T cells and, in total, 59% of patients with congenital immunodeficiency were positive for somatic mutations in CD4 + or CD8 + T cells, which would be expected to have deleterious effects on the cellular functions of T cells (Figure 1).…”
mentioning
confidence: 99%
See 1 more Smart Citation